Find answers to your questions faster and easier with IDNLearn.com. Join our interactive Q&A community and access a wealth of reliable answers to your most pressing questions.
Sagot :
To simplify the given expression [tex]\(\left(5 x y^5\right)^2\left(y^3\right)^4\)[/tex], we can follow these steps:
1. Simplify [tex]\(\left(5 x y^5\right)^2\)[/tex]:
Raise [tex]\(5 x y^5\)[/tex] to the power of 2. This means we need to square each of the factors inside the parentheses.
[tex]\[ \left(5 x y^5\right)^2 = (5)^2 \cdot (x)^2 \cdot (y^5)^2 \][/tex]
Calculate each part separately:
[tex]\[ (5)^2 = 25 \][/tex]
[tex]\[ (x)^2 = x^2 \][/tex]
[tex]\[ (y^5)^2 = y^{5 \cdot 2} = y^{10} \][/tex]
Combine these results:
[tex]\[ \left(5 x y^5\right)^2 = 25 x^2 y^{10} \][/tex]
2. Simplify [tex]\(\left(y^3\right)^4\)[/tex]:
Raise [tex]\(y^3\)[/tex] to the power of 4. Multiply the exponent inside the parentheses by the exponent outside.
[tex]\[ \left(y^3\right)^4 = y^{3 \cdot 4} = y^{12} \][/tex]
3. Multiply the simplified parts:
Combine the simplified expressions [tex]\(\left(5 x y^5\right)^2 = 25 x^2 y^{10}\)[/tex] and [tex]\(\left(y^3\right)^4 = y^{12}\)[/tex].
[tex]\[ 25 x^2 y^{10} \cdot y^{12} \][/tex]
Since the bases of the [tex]\(y\)[/tex] terms are the same, we add the exponents:
[tex]\[ 25 x^2 y^{10 + 12} = 25 x^2 y^{22} \][/tex]
Therefore, the correct simplification of the expression [tex]\(\left(5 x y^5\right)^2\left(y^3\right)^4\)[/tex] is:
[tex]\[ \boxed{25 x^2 y^{22}} \][/tex]
1. Simplify [tex]\(\left(5 x y^5\right)^2\)[/tex]:
Raise [tex]\(5 x y^5\)[/tex] to the power of 2. This means we need to square each of the factors inside the parentheses.
[tex]\[ \left(5 x y^5\right)^2 = (5)^2 \cdot (x)^2 \cdot (y^5)^2 \][/tex]
Calculate each part separately:
[tex]\[ (5)^2 = 25 \][/tex]
[tex]\[ (x)^2 = x^2 \][/tex]
[tex]\[ (y^5)^2 = y^{5 \cdot 2} = y^{10} \][/tex]
Combine these results:
[tex]\[ \left(5 x y^5\right)^2 = 25 x^2 y^{10} \][/tex]
2. Simplify [tex]\(\left(y^3\right)^4\)[/tex]:
Raise [tex]\(y^3\)[/tex] to the power of 4. Multiply the exponent inside the parentheses by the exponent outside.
[tex]\[ \left(y^3\right)^4 = y^{3 \cdot 4} = y^{12} \][/tex]
3. Multiply the simplified parts:
Combine the simplified expressions [tex]\(\left(5 x y^5\right)^2 = 25 x^2 y^{10}\)[/tex] and [tex]\(\left(y^3\right)^4 = y^{12}\)[/tex].
[tex]\[ 25 x^2 y^{10} \cdot y^{12} \][/tex]
Since the bases of the [tex]\(y\)[/tex] terms are the same, we add the exponents:
[tex]\[ 25 x^2 y^{10 + 12} = 25 x^2 y^{22} \][/tex]
Therefore, the correct simplification of the expression [tex]\(\left(5 x y^5\right)^2\left(y^3\right)^4\)[/tex] is:
[tex]\[ \boxed{25 x^2 y^{22}} \][/tex]
We greatly appreciate every question and answer you provide. Keep engaging and finding the best solutions. This community is the perfect place to learn and grow together. Your search for answers ends at IDNLearn.com. Thank you for visiting, and we hope to assist you again soon.